Geastrum trichiferum and Geastrum setiferum (Geastrales, Phallomycetidae) new records for Argentina - Castiglia, Valeria Carolina (2013)
In the present study two new records of Geastrum are reported for Argentina: G. trichiferum Rick and G. setiferum Baseia. Descriptions, comments and illustrations of basidiomata are given.